Achieving Pure Deep‐Blue Electroluminescence with CIE y≤0.06 via a Rational Design Approach for Highly Efficient Non‐Doped Solution‐Processed Organic Light‐Emitting Diodes. Issue 22 (14th October 2016) - Reddy, Saripally Sudhaker; Sree, Vijaya Gopalan; Cho, Woosum; Jin, Sung‐Ho
Abstract: Deep‐blue fluorescent emitters with Commission Internationale de l'Eclairage (CIE) y ≤0.06 are urgently needed for high‐density storage, full‐color displays and solid‐state lighting. However, developing such emitters with high color purity and efficiency in solution‐processable non‐doped organic light‐emitting diodes (OLEDs) remains an important challenge. Here, we present the synthesis of two new deep‐blue fluorescent emitters (AFpTPI andAFmTPI ) based on 10‐(9, 9‐diethyl‐9H‐fluoren‐2‐yl)‐9, 9‐dimethyl‐9, 10‐dihydroacridine as a core and 1, 3‐ and/or 1, 4‐phenylene‐linked triphenylimidazole (TPI) analogues for non‐doped solution‐processable OLEDs. Their thermal, photophysical, electrochemical, and device characteristics are explored, and also strongly supported by density functional theory (DFT) study.AFpTPI andAFmTPI exhibit excellent thermal stability (≈450 °C) with high glass transition temperatures ( T g ; 141–152 °C) and deep‐blue emission with high quantum yields. Specifically, the solution‐processed non‐doped device withAFpTPI as an emitter exhibits a maximum external quantum efficiency (EQE) of 4.56 % with CIE coordinates of (0.15, 0.06), which exactly matches the European Broadcasting Union (EBU) blue standard. In addition, AFmTPI also displays good efficiency and better color purity (EQE: 3.37 %; CIE (0.15, 0.05)). To the best of our knowledge, the present work is the first report on non‐doped solution‐processable OLEDs with efficiency close to 5 % and CIE y≤0.06. Abstract : Into the deep blue : Deep‐blue fluorescent emitters based on 10‐(9, 9‐diethyl‐9H‐fluoren‐2‐yl)‐9, 9‐dimethyl‐9, 10‐dihydroacridine as a core and 1, 3‐ and/or 1, 4‐phenylene‐linked triphenylimidazole analogues are designed and synthesized for non‐doped solution‐processable OLEDs. They delivered both a good efficiency and excellent color purity with CIE y≤0.06, which well matches the European Broadcasting Union (EBU) blue standard.